Variations on the bilingual advantage? Links of Chinese and English proficiency to Chinese American children's self-regulation - Chen, Stephen H.; Zhou, Qing; Uchikoshi, Yuuko; Bunge, Silvia A. (Frontiers in Psychology, 2014)
The present study examined whether bilingualism-related advantages in self-regulation could be observed: (a) among Chinese American immigrant children with varying levels of Chinese and English proficiencies, and (b) across different domains of self-regulation in laboratory, home, and classroom contexts. A socioeconomically diverse sample of first- and second-generation Chinese American immigrant children between ages 7 and 10 (n = 223) was administered assessments of Chinese and English language proficiencies and a multi-method, multi-informant battery of self-regulation measures. Multiple regression analyses suggested that controlling for covariates (child age, gender, and SES), children's bilingualism-related advantages were limited to higher performance only on computerized tasks of cognitive flexibility, and only among children with higher degrees of fluency in both Chinese and English. By contrast, proficiencies in one language (either Chinese or English) were uniquely and positively associated with other domains of self-regulation, including parent and teacher-reported effortful control. These results suggest that the bilingual advantage for self-regulation may be observed as a continuous variable among immigrant children with varying levels of bilingual fluency; however, this advantage may not extend across all domains and contexts of self-regulation.